The Mismatch between Knowledge and Belief: A Comparative Study of Students' Conceptual Understanding and Confidence in the Topic of Center of Gravity - Irawan, Dani; Tohir, M. Anas; Wahab, Nadia Abdul (Indonesian Review of Physics, 2024)
This study explores the discrepancy between conceptual understanding and confidence levels among mechanical engineering students regarding the concept of the center of gravity. Despite its importance in physics, students frequently hold misconceptions about the center of gravity, particularly in irregular objects and composite shapes. Using a novel five-tier diagnostic instrument, this research measured students' understanding and confidence in their responses and reasons. The findings revealed that 12% of students had misconceptions and revised their personal thoughts as the most recurring error source. Furthermore, a sizeable group of students demonstrated an illusion of knowing something high wherein they were very sure but wrong! This should serve to prove the importance of teacher educational reforms, which support overturning misconceptions and correctness of levels of confidence of students to a corresponding realistic base. Knowledge and beliefs were further intertwined through the analysis of the Rasch model, in a bid to understand this relationship. The reported results also increase knowledge in physics instruction because they provide practical ways of minimizing misconceptions as well as an effective teaching profession, especially on the topic of center of gravity. This paper highlights how addressing both conceptual and psychological factors when students are learning can help them in physics education. By integrating psychological and conceptual dimensions into teaching strategies, educators can enhance students' grasp of foundational concepts like the center of gravity and improve their overall learning outcomes in physics and engineering contexts. This research contributes to the development of evidence-based instructional practices aimed at minimizing misconceptions and fostering deeper, more accurate learning.